The Literary Appreciation Level of Students - Febrianty, Fenny; Hafiz, Muhammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The study aimed to determine the literary appreciation level of students. The object of the research was first-year students. This research is a case study with a direct interpretation method. The data collection tool was an online questionnaire. There were several literary appreciation levels for students namely appreciation level, understanding level, comprehension level, and implication level. The small percentage of students who reach the implication level as the ultimate goal of literary appreciation activities as well as the various obstacles encountered at each level of literary appreciation will be used as a reference in the evaluation of literary appreciation learning in the fifth semester